186k views
0 votes
Y = x + 4

y = −2x − 2

Explain how you will solve the pair of equations by substitution. Show all the steps and write the solution in (x, y) form. explain

User Piuspbd
by
5.6k points

2 Answers

4 votes

Answer:

(-2, 2).

Explanation:

y = x + 4

y = -2x - 2

Substitute y = x + 4 in the second equation:

x + 4 = -2x - 2

x + 2x = -2 - 4

3x = -6

x = -2.

To get the value of y we substitute x = -2 in the first equation:

y = -2 + 4

y = 2.

Check the result by substituting for x and y in the second equation:

y = -2x - 2

2 = -2(-2) - 2

= 4 - 2 = 2.

- checked.

User Charles DB
by
5.3k points
3 votes

Answer:

(-2,2)

Explanation:

the value of "y" is already given so lets substitute that in the second equation:

x+4=-2x-2

2) bring all like terms to one side

x+2x=-4-2

3x=-6

x=-2

substitute "-2" as "x" in the first equation:

y=(-2)+4

y=2

Hope this helps!

User Kenisha
by
5.5k points